"This is not nostalgia": Contesting the Politics of Sentimentality in Boston's 2004 Parish Closure Protests - Reynolds, Susan Bigelow (US catholic historian, 2023)
In 2004, the Catholic Archdiocese of Boston announced the closure or merger of nearly a quarter of its parishes in a massive reconfiguration process. Some Catholics responded with protests, staging prolonged church occupations and Vatican appeals to save their parishes. Though these protests garnered significant public sympathy and media attention, most were unsuccessful in preventing closure. Yet one grassroots campaign succeeded where many well-resourced resistance efforts did not. At St. Mary of the Angels—a small, eclectic, basement-level church in Egleston Square, a Black and Latino neighborhood in Roxbury—parishioners and community leaders launched a solidarity campaign to persuade the archdiocese that closing St. Mary's would decimate longstanding efforts to combat neighborhood violence. Whereas other anti-closure protests stressed parishioners' personal and familial attachments to their churches, St. Mary's campaign strategically eschewed the politics of sentimentality, emphasizing instead the congregation's crucial role in the local urban ecology. Drawing on interviews and archdiocesan and community archives, this study of the efforts to save St. Mary's demonstrates the overlooked significance of ecumenical, interfaith, and secular relationships in sustaining urban parishes. At the same time, it underscores the roles of race, class, and immigration in shaping public attention to church closures.